Conformational effects of N-glycan core fucosylation of immunoglobulin G Fc region on its interaction with Fcγ receptor IIIa - Sakae, Yoshitake; Satoh, Tadashi; Yagi, Hirokazu; Yanaka, Saeko; Yamaguchi, Takumi; Isoda, Yuya; Iida, Shigeru; Okamoto, Yuko; Kato, Koichi (Scientific reports, 2017)
Antibody-dependent cellular cytotoxicity (ADCC) is promoted through interaction between the Fc region of immunoglobulin G1 (IgG1) and Fcγ receptor IIIa (FcγRIIIa), depending on N -glycosylation of these glycoproteins. In particular, core fucosylation of IgG1-Fc N -glycans negatively affects this interaction and thereby compromises ADCC activity. To address the mechanisms of this effect, we performed replica-exchange molecular dynamics simulations based on crystallographic analysis of a soluble form of FcγRIIIa (sFcγRIIIa) in complex with IgG1-Fc. Our simulation highlights increased conformational fluctuation of the N -glycan at Asn162 of sFcγRIIIa upon fucosylation of IgG1-Fc, consistent with crystallographic data giving no interpretable electron density for this N -glycan, except for the innermost part. The fucose residue disrupts optimum intermolecular carbohydrate-carbohydrate interactions, rendering this sFcγRIIIa glycan distal from the Fc glycan. Moreover, our simulation demonstrates that core fucosylation of IgG1-Fc affects conformational dynamics and rearrangements of surrounding amino acid residues, typified by Tyr296 of IgG1-Fc, which was more extensively involved in the interaction with sFcγRIIIa without Fc core fucosylation. Our findings offer a structural foundation for designing and developing therapeutic antibodies with improved ADCC activity.